2021
DOI: 10.3390/ijerph18094396
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of an Acceptance and Commitment Therapy and Mindfulness Group Intervention for Enhancing the Psychological and Physical Well-Being of Adults with Overweight or Obesity Seeking Treatment: The Mind&Life Randomized Control Trial Study Protocol

Abstract: Although several interventions that target obesity have been examined, the success of these interventions in generating and maintaining positive results has yet to be confirmed. This study protocol therefore presents a trial aimed at analyzing the effectiveness of a well-being-centered acceptance and commitment therapy (ACT)- and mindfulness-based group intervention following the valued-based healthy living (VHL) approach (Mind&Life intervention) for individuals experiencing overweight-related distress. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 65 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…This study is part of the Mind&Life project (Iturbe et al, 2021), which has the approval of the Ethics Committee of the Basque Health Service (protocol code: MAI-MIN-2018-01). While snowball sampling was used to recruit some participants, the subsample used to study sensitivity to change was recruited from primary care units of the area.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study is part of the Mind&Life project (Iturbe et al, 2021), which has the approval of the Ethics Committee of the Basque Health Service (protocol code: MAI-MIN-2018-01). While snowball sampling was used to recruit some participants, the subsample used to study sensitivity to change was recruited from primary care units of the area.…”
Section: Methodsmentioning
confidence: 99%
“…The online platform used for data collection was Encuesta Fácil (https://www.encuestafacil.com). Regarding the recruitment of the sample derived from primary care units, the principal researchers of the Mind&Life study to which the present investigation adheres previously contacted medical and nursing professionals of the service to inform people seeking weight management treatment about the Mind&Life study (Iturbe et al, 2021). If interested in participating, they would contact study investigators, who would ensure that the inclusion criteria were met.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…MBIs emphasize the nonjudgmental focus on and awareness of the present moment, emotional and behavioral self-regulation, and mindfulness meditation practice [ 19 ], and they are appropriate for university students because they are easily learned and can be practiced conveniently in daily life, which increases resilience to stress [ 20 ]. Additionally, MBI with groups has become increasingly popular within universities, since researchers have confirmed that group-based interventions have significant influence on the alleviation of psychological symptoms [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%